Virtual reality consumer experience escapes: preparing for the metaverse - Han, Dai-In Danny; Bergs, Yoy; Moorhouse, Natasha (Virtual reality : the journal of the Virtual Reality Society, 2022)
Virtual Reality (VR) experience escapes allow individuals to spend hours on end in immersive virtual environments and interact with content in a world that is providing shelter and illusion of an alternative reality – the metaverse. Discussions on possible risks have largely remained limited to usability challenges, while only a few studies reflect on social, psychological and physical implications this immersive technology exposes and the considerations consumers and businesses need to take. This paper critically reviews literature on escapism to discuss issues in the design and employment of virtual reality consumer experience escapes. Key issues relating to VR experience escapes and resulting effects on consumer health and well-being are discussed, emphasizing needed consumer-centered research and design. Future considerations include (1) Self-indulgent escapism through VR consumer experiences, (2) Ethical considerations in the design of VR consumer experience escapes, and (3) Purposeful design of VR consumer experiences escapes. A sequential research agenda is presented that integrates antecedents of VR experience escapes that connect to three main future research streams; designing purpose-driven VR consumer experience escapes, complementing methodologies for VR consumer experience research, and meaningful VR consumer experience escapes.